Dampak Keterbatasan Akses Pendidikan terhadap Relevansi Sosial di Desa Cibaliung, Rokan Hilir, Riau - Putra, M. Jaya Adi; Handoko, Tri; Alfita, Adinta; Meisyaharta, Chyntia; Sari, Dian Alpita; Nuralia, Feby; Meuthiasyah, Shyfa; Afirli, Wulan (Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the impact of limited access to education on the sustainability of social relevance of the community in Cibaliung Village, Balai Jaya District, Rokan Hilir Regency, Riau. The methods used are field observation, interviews with residents, and analysis of relevant documentation. The results show that limited educational facilities, infrastructure conditions, and low community economy greatly affect children's participation in formal education. This has implications for low social mobility and inequality of access to information and skills in the community. Community involvement and government support are key to increasing the relevance of education in the village.